Islamisasi Pengetahuan Syed Naquib Al-Attas dan Ismail Al-Faruqi - Coil, Coil; Aprison, Wedra (YASIN, 2023)
Echols and Hasan Sadily stated that the term "Islamization" comes from the English word "islamization", which means "to convert." When someone hears the word "Islamization of Science", some people feel that certain knowledge is not in accordance with Islam, so it must be Islamized. The two main figures, Syed Muhammad Naquib Al-Attas and Ismail Raji Al Faruqi, are usually the center of attention when people talk about the Islamization of science. In terms of epistemology, al-Attas and al-Faruqi agree that science is not value-free but bound by values that are considered true. They also agree that science has the same goal, and its conception is based on the principles of metaphysics, ontology, epistemology, and axiology with monotheism as the key. While there are many similarities between the two, they differ in several fundamental ways. To achieve the success of the goal of Islamization, al-Attas places more emphasis on the subject than knowledge, namely humans, by cleansing the soul and adorning it with commendable qualities, so that the process of Islamization of knowledge will result in personal transformation as well as spiritual and Islamic Islam as a whole. However, al-Faruqi put more emphasis on the subject intended to be Islamized, namely the discipline itself.